The Relationship Between Strength of the Affected Leg and Walking Speed After Stroke Varies According to the Level of Walking Disability: A Systematic Review. Issue 12 (6th October 2021) - Dorsch, Simone; Ada, Louise; Sorial, Tiffany; Fanayan, Emma
ABSTRACT: Objective: The objectives of this review were to determine the relationship between muscle strength of the affected leg and walking speed after stroke and whether this relationship varied according to muscle group or level of walking disability. Methods: This systematic review with meta-analysis focused on observational studies of adult survivors of stroke. Muscle strength had to be measured as maximum voluntary force production during an isometric contraction of the affected leg. Walking had to be measured as walking speed. Studies had to report correlations between muscle strength and walking speed. Results: Thirty studies involving 1001 participants were included. Pooled mean correlations between muscle strength of the affected leg and walking speed was 0.51 (95% CI = 0.45 to 0.57). Pooled correlations between the strength of individual muscle groups and walking speed ranged from 0.42 (for the hip abductors) to 0.57 (for the ankle dorsiflexors). The correlation between level of walking disability and the mean correlation between muscle strength and walking speed was −0.70 (95% CI = −0.42 to −0.86). Conclusion: After stroke, there is a strong relationship between strength of the affected leg and walking speed, with little variability across individual muscle groups. However, the level of walking disability of people with stroke does make a difference such that the more disabled people are, the stronger the relationship is between strength of the affected leg and walking speed. Impact: This study suggests that the strength of all muscles of the affected leg is important for walking after stroke. It appears that increasing strength in the affected leg could be most important in people who are more disabled. Lay Summary: After stroke, the speed at which a person can walk is highly associated with the muscle strength of their affected leg. In people whose walking speed is severely affected, this association is stronger, and the physical therapist might focus on strengthening that leg so the individual can walk faster.